Peran Media Online Lokal dalam Pembentukan Opini Publik melalui Pemberitaan Politik - Srimudin, Agus; Putri, Intan; Negara, Kemas Umar Jaya; Novasriady, Novasriady; Hikmawati, Mutiara (Jurnal Publisitas, 2026)
This study is motivated by the strategic role of online media in constructing political reality at the local level, particularly in Palembang City. The research problem focuses on how media frame political issues and the implications of such framing for public opinion formation. This study aims to analyze framing patterns in local online political news coverage and to identify the dominant tendencies in political representation. The research employs a qualitative approach using the framing analysis model of Robert N. Entman on 28 purposively selected political news articles. The analysis is conducted through four framing elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The findings indicate that the media tend to frame local politics in a stability-oriented, moderate, and affirmative manner toward local government policies. Politics is represented as a conducive and well-managed sphere, with minimal emphasis on conflicts involving key political actors or substantive criticism of policies. These findings confirm that media actively shape public opinion through structured mechanisms of issue selection and emphasis. The implications of this study are both theoretical and practical, reinforcing the relevance of framing theory in local political communication studies and providing reflection for media practitioners and stakeholders on the importance of balanced reporting in maintaining the quality of local democracy.